1996
DOI: 10.1007/s004210050119
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle buffering capacity and endurance performance after high-intensity interval training by well-trained cyclists

Abstract: Skeletal muscle buffering capacity (beta m), enzyme activities and exercise performance were measured before and after 4 weeks of high-intensity, submaximal interval training (HIT) undertaken by six well-trained competitive cyclists [mean maximal oxygen consumption (VO2max) = 66.2 ml.kg-1.min-1]. HIT replaced a portion of habitual endurance training and consisted of six sessions, each of six to eight repetitions of 5 min duration at 80% of peak sustained power output (PPO) separated by 1 min of recovery. beta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
183
7
24

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(229 citation statements)
references
References 46 publications
15
183
7
24
Order By: Relevance
“…It is widely thought that muscle buffering capacity affect the short-time high intensity exercise performance (Parkhouse et al, 1985;Denis et al, 1992). However, Weston et al (1997) reported that bicycle athletes performing 80% peak power output (PPO) intensity interval training signifi cantly increased skeletal muscle buffering capacity. Those who showed greater increase rate in skeletal muscle buffering capacity tended to improve in time in a 40 km time trial.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely thought that muscle buffering capacity affect the short-time high intensity exercise performance (Parkhouse et al, 1985;Denis et al, 1992). However, Weston et al (1997) reported that bicycle athletes performing 80% peak power output (PPO) intensity interval training signifi cantly increased skeletal muscle buffering capacity. Those who showed greater increase rate in skeletal muscle buffering capacity tended to improve in time in a 40 km time trial.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Sharoff et al (2006) observed no difference in performance at 90% W max after a 50-min constant work period (at 60% VO 2max ). During the exercise of the nature and duration described above, CHO stress is unlikely to limit performance, and factors such as muscle buffer capacity are arguably more important (Weston et al, 1997). The effect of galactose supplementation on exercise performance of a longer duration remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Buffering capacity is associated with improved exercise performance and increased resistance to fatigue (Weston et al, 1997). A higher muscle buffer value should allow a more prolonged utilization of anaerobic glycolysis before a limiting pH is reached (Parkhouse and McKenzie, 1 9 8 4 ) .…”
Section: Resultsmentioning
confidence: 99%